PENGURANGAN CHROM (Cr) DALAM LIMBAH CAIR INDUSTRI KULIT PADA PROSES TANNERY MENGGUNAKAN SENYAWA ALKALI Ca(OH)2, NaOH DAN NaHCO3 (STUDI KASUS PT. TRIMULYO KENCANA MAS SEMARANG) - Asmadi, Asmadi; S, Endro; Oktiawan, W. (Jurnal Air Indonesia, 2009)
AbstractOne of the industries that use hazardous and toxic (B3) on the production process is leather tannery industry, with a compound chromium (Cr). Chromium in the compound, including heavy metals that have a known toxicity of high power. Alkali compound is Ca(OH)2, NaOH,and NaHCO3 the chemicals that can be used for processing liquid waste leather tannery industry that contains chromium, which works to raise the pH and precipitate chromium solution so produced chrome hidroksida in the form of chromium (Cr(OH)3). Results of research it was found that the pH optimum for alkali compound at each pH condition 8, the separation efficiency of 99.28% chromium compound using alkali Ca (OH) 2 and NaOH, while the use of 98.50% NaHCO3. Alkali compound which most effective review of technical aspects to a decrease in the concentration of chromium in leather tannery wastewater is NaOH, because with a small dose is able to separate the chromium in the wastewater with a high efficiency (99.28%), while the most economical and is recommended for applications is in the Ca(OH)2. Key words : Ca(OH)2, Cr2O3, separation efficiency, hidroksida chromium (Cr(OH)3), NaHCO3, NaOH, pH optimum, alkali compound.